KETERWAKILAN PEREMPUAN SEBAGAI PENYELENGGARAPEMILU MENUJU PESTA DEMOKRASI 2024 - Hajriana Hajriana; Riska Riska (Jurnal Syariah Hukum Islam, 2020)
In Article 28D of the Constitution of the Republic of 1945 Indonesia paragraph (3) which reads, "Every citizen has the right to equal opportunities in government". The composition of women's representation of 30% of the KPU RI and Bawaslu RI election organizers for the 2024 elections has not been fulfilled. So this is considered a setback for the women's representation movement. This research was conducted using normative methods with a statute approach and a conceptual approach approach. So according to data on the percentage of women's representation in every province in Indonesia, none of them have reached the minimum number, even though the presence of women in election organizers has two interests. First, the political interests of women in the public sphere, namely the organizers of elections. Second, the interest of maintaining women's representation at the nomination stage to the electability of women through national, permanent, and independent election organizing institutions